Amentoflavone as an Ally in the Treatment of Cutaneous Leishmaniasis: Analysis of Its Antioxidant/Prooxidant Mechanisms - Rizk, Yasmin Silva; Santos-Pereira, Sandy; Gervazoni, Luiza; Hardoim, Daiana de Jesus; Cardoso, Flávia de Oliveira; de Souza, Celeste da Silva Freitas; Pelajo-Machado, Marcelo; Carollo, Carlos Alexandre; de Arruda, Carla Cardozo Pinto; Almeida-Amaral, Elmo Eduardo; Zaverucha-do-Valle, Tânia; Calabrese, Kátia da Silva (Frontiers in Cellular and Infection Microbiology, 2021)
Treatment of leishmaniasis is a challenging subject. Although available, chemotherapy is limited, presenting toxicity and adverse effects. New drugs with antileishmanial activity are being investigated, such as antiparasitic compounds derived from plants. In this work, we investigated the antileishmanial activity of the biflavonoid amentoflavone on the protozoan Leishmania amazonensis. Although the antileishmanial activity of amentoflavone has already been reported in vitro, the mechanisms involved in the parasite death, as well as its action in vivo, remain unknown. Amentoflavone demonstrated activity on intracellular amastigotes in macrophages obtained from BALB/c mice (IC50 2.3 ± 0.93 μM). No cytotoxicity was observed and the selectivity index was estimated as greater than 10. Using BALB/c mice infected with L. amazonensis we verified the effect of an intralesional treatment with amentoflavone (0.05 mg/kg/dose, in a total of 5 doses every 4 days). Parasite quantification demonstrated that amentoflavone reduced the parasite load in treated footpads (46.3% reduction by limiting dilution assay and 56.5% reduction by Real Time Polymerase Chain Reaction). Amentoflavone decreased the nitric oxide production in peritoneal macrophages obtained from treated animals. The treatment also increased the expression of ferritin and decreased iNOS expression at the site of infection. Furthemore, it increased the production of ROS in peritoneal macrophages infected in vitro. The increase of ROS in vitro, associated with the reduction of NO and iNOS expression in vivo, points to the antioxidant/prooxidant potential of amentoflavone, which may play an important role in the balance between inflammatory and anti-inflammatory patterns at the infection site. Taken together these results suggest that amentoflavone has the potential to be used in the treatment of cutaneous leishmaniasis, working as an ally in the control and development of the lesion.